Explore a spooky swamp - Cortesi, Wendy W., 1941-; Bailey, Joseph H. ([Washington] : National Geographic Society, 1978)
Two youngsters discover the varied plants and animals that make their home in the watery world of the swamp.
Keywords: Swamp ecology -- Juvenile literature; Swamp ecology; Ecology